Effect of intranasal mometasone furoate administered in children with coexisting allergic rhinitis and asthma towards asthma attacks and lung function - Ellen P. Gandaputra; Zakiudin Munasir; Bambang Supriyatno; Jose R. L. Batubara (Indonesian Pediatric Society, 2009)
Background Allergic rhinitis and asthma are allergic manifestations in respiratory tract, which related each other. Intranasal corticosteroid is effective in allergic rhinitis and has benefits in decreasing lower airway reactivity.Objectives To evaluate effectiveness of intranasal mometasonefuroate towards asthma in children aged 6-18 years with coexisting allergic rhinitis and asthma.Methods A one group pretest-posttest (